1998
DOI: 10.1159/000013403
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone-Producing Adrenocortical Adenoma Complicated by Chronic Renal Failure

Abstract: A 61-year-old Japanese woman was hospitalized because of general malaise. The patient demonstrated hypertension, hypokalemia and chronic renal failure (CRF). Plasma aldosterone concentration and urinary excretion of aldosterone were elevated. Abdominal computed tomographic scan revealed right adrenal tumor and multiple cysts in both kidneys. Adrenal scintigram using 131I-adosterol disclosed uptake of the isotope in the area corresponding to the adrenal tumor. Plasma aldosterone concentration and ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…A previous study has shown that creatinine clearance correlates inversely with PRA in patients with PA, indicating that PRA tends to be higher in PA patients with renal failure (9). There have been several reports on PA cases with renal failure (7,8,11-18). To our knowledge, however, only 6 PA cases with a clinical course similar to that of the present case (i.e., PA with renal failure, accelerated-malignant hypertension, increased PRA, and false-negative result of PAC/PRA ratio) have been reported (11-16).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that creatinine clearance correlates inversely with PRA in patients with PA, indicating that PRA tends to be higher in PA patients with renal failure (9). There have been several reports on PA cases with renal failure (7,8,11-18). To our knowledge, however, only 6 PA cases with a clinical course similar to that of the present case (i.e., PA with renal failure, accelerated-malignant hypertension, increased PRA, and false-negative result of PAC/PRA ratio) have been reported (11-16).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early treatment of PA can effectively reduce the morbidity and mortality of cardiovascular and cerebrovascular diseases. For some patients with special conditions, such as PA during pregnancy and elderly patients, drug therapy is more appropriate ( 25 , 26 ). Study have shown that in tumor cells, the WNT pathway is overactivated often due to gene mutations, and a large number of β-catenin proteins enter the nucleus for TCF/LEF transcriptional regulation ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of PA in patients with CKD is difficult and easily missed, and only 2 cases have been reported in the English literature [20, 21]. This is because CKD masks the typical hallmarks of PA (hypertension, hypokalemia, and low PRA), shares some features with PA (such as hypertension and elevated PAC) [22], and disturbs the renin-angiotension-aldosterone system leading to a further decrease of the response of renin/aldosterone to stimuli or suppressive manoeuvres [23].…”
Section: Discussionmentioning
confidence: 99%